Edna's Struggle Against Oppressions in The Awakening - Adhikari, Tara Prasad (Pursuits: A Journal of English Studies, 2024)
This study explores Edna Pontellier's struggle against societal oppressions in Kate Chopin's novel, The Awakening. Edna's quest for self-discovery and liberation from the constraints of late 19th-century societal norms is analyzed through the lens of feminist perspectives. This paper argues that Edna's unconventional behavior signifies a profound challenge to patriarchal norms, emphasizing her pursuit of identity and autonomy. Edna emerges as a symbol of resistance against societal expectations, seeking personal freedom amidst oppressive forces. Furthermore, the study explores the influence of characters like Adele Ratignolle and Mademoiselle Reisz on Edna's journey, highlighting contrasting paths of womanhood and autonomy.